Corporate social responsibility funding and its impact on India's sustainable development: Using the poverty score as a moderator - Rahul Singh Gautam; Venkata Mrudula Bhimavarapu; Shailesh Rastogi; Jyoti Mehndiratta Kappal; Hitesh Patole; Aman Pushp (Journal of Risk and Financial Management, 2023)
This study investigates the impact of corporate social responsibility (CSR) funding in the education sector and the environment and how it affects India's sustainable development. This study was conducted using secondary data and the data were collected from 28 Indian states and three union territories for the four fiscal years 2018 to 2021. This study examines the hypothesis using the generalized method of moments (GMM). As a result, it is found that overall CSR funding positively contributes to India's sustainable development. Additionally, this study finds that CSR funding in education and the environment supports India's sustainable development. It is also observed that, under the interaction effect of poverty (poverty score), CSR funding (total) and CSR funding on education positively affect sustainable growth. However, CSR funding for environmental activities does not significantly influence India's FD under the moderation of poverty score. These factors are essential for India's sustainable development and poverty reduction. Investing CSR funds in rural development, education, the environment, health, and other areas supporting India's sustainable development leads to impressive economic growth and reduces poverty. Hence, it is attributed that CSR funding plays a vital role in India's sustainable development. Future research can be carried out on CSR policies and funding using different variables and periods.
Keywords: 650; CSR; panel data; education and environment; poverty; SDG